Habitual dietary intake of fatty acids are associated with leptin gene expression in subcutaneous and visceral adipose tissue of patients without diabetes. (November 2017) - Rostami, Hosein; Samadi, Mohammad; Yuzbashian, Emad; Zarkesh, Maryam; Asghari, Golaleh; Hedayati, Mehdi; Daneshafrooz, Afsoon; Mirmiran, Parvin; Khalaj, Alireza
Abstract: The purpose of the study was to investigate the association of leptin gene expression in visceral and subcutaneous adipose tissues with habitual fatty acid intake and its subtypes in adults. Visceral and subcutaneous adipose tissues were gathered from 97 participants aged ≥ 20, who had undergone elective abdominal surgery. Dietary fatty acid intakes including total fatty acids (TFA), saturated fatty acid (SFA), monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA), n-3, n-6, and n-9 fatty acids were collected using a valid and reliable food-frequency questionnaire (FFQ). The leptin gene expression in visceral and subcutaneous adipose tissues was measured by Real-Time PCR. After controlling for body mass index (BMI) and insulin, energy-adjusted dietary intake of SFA was positively and MUFA and n-3 fatty acids were negatively associated with subcutaneous and visceral adipose tissues leptin gene expression. Besides, a significant negative association of PUFA, n-6, and n-9 fatty acids with leptin mRNA from visceral adipose tissue were observed. In order to better interpretations of the results, the participants were allocated two groups including non-obese (BMI < 30 kg/m 2 ) and obese subjects (BMI ≥ 30 kg/m 2 ). Among non-obese participants, the SFA had positive and PUFA had negative association with leptin gene expression in both adipose tissues. Furthermore, in obese participants, n-3, n-6, and n-9 fatty acids had a negative association with visceral leptin gene expression. Habitual intake of SFA, MUFA, and n-3 fatty acids were associated with leptin gene expression in visceral and subcutaneous adipose tissues, suggesting an important role of quality and quantity of fatty acids intake in adipose tissue to regulate leptin expression. Highlights: Dietary intake of SFA was positively and MUFA was negatively associated with leptin gene expression from subcutaneous and visceral adipose tissue. Dietary intake of SFA was positively associated and of n-3 fatty acids, n-6 fatty acids, and n-9 fatty acids was negatively associated with leptin mRNA from visceral adipose tissue. MUFA and n-3 fatty acids had a negative association with subcutaneous, and MUFA, PUFA, and n-3 fatty acids had a negative association with visceral leptin gene expression.